The plausible pathway of air pollutants and the respiratory system among COVID-19 patients: a systematic literature review - Wardono, Hari Rudijanto Indro; Susanti, R; Wijayanti, Yuni; Cahyati, Widya Hari (International Journal of Public Health Science (IJPHS), 2024)
Studies evidence links air pollution to increased risk of COVID-19 infection and severity during the pandemic. Nonetheless, those studies are unable to discuss specific pollutants, such as particulate matter, Sox, and NOx. This systematic literature review aimed to summarize the most recent studies on the links between pollutants and their effects on the respiratory system, in this case, mostly on COVID-19 patients. We searched using electronic databases (PubMed, Springer, ScienceDirect, and Sage) in May 2023. The keywords chosen were connected to respiratory diseases and air pollution. All relevant studies published in peer-reviewed journals between 2020 and 2023 and written in English were considered. We excluded letters and non-original articles. Relevant keywords were used to select papers. A total of 11 articles are eligible to be included in the present review study. It was reported that countries with a high prevalence of COVID-19 also have greater concentrations of surface air particles (PM10 and PM2.5) due to vehicle exhaust and industrial pollution. PM-virus aggregates spread easier across the lungs and the top respiratory system, facilitating viral attachment to the lung epithelium. This study found that tiny particles with an aerodynamic dimension fewer than 2.5 μm (PM2.5) or ten μm (PM10) have the most significant potential influence on the respiratory system compared to other pollutants.